“Optimización del Rendimiento de un Motor CG200 Mediante el Acoplamiento de un Variador de Posición en el Cigüeñal”. - Ayala Lamar, Alexander Fernando (2022)
It consists of improving the performance of a low cylinder capacity motorcycle cg200 (throttle cylinder) by adapting an external crankshaft cg200 (throttle cylinder) with the same characteristics without a gearbox, so increasing the cylinder capacity motorcycle to a cg400 (throttle cylinder). The two crankshafts will be joined horizontally by a belt to reduce the torque in the crankshafts, avoiding the effort exerted by a single engine crankshaft and lengthening its useful life. It will improve abrasive wear and its maintenance is profitable and economical due to the fact that the spare parts are inexpensive and they can be easily found in markets. Topics that describe the technical part of the motorcycle are covered, such as: performance, power, final speed, compression and its performance; all of these aspects cover the technical sheet with the corresponding data and show with graphs, tables, and diagrams of the engine's operation. One of the reasons that drive this project is the excessive price of medium cylinder capacity motorcycles. It is taken into account the involved costs in the manufacture of the parts in the design of the motorcycle and its commercial cost in order to show real data on the feasibility of assembling this type of motorcycle in Ecuador. It will be checked if it is profitable to optimize a low cylinder capacity engine or to buy a medium cylinder capacity engine according to the prices of motorcycles in the Ecuadorian market and to compare with the expenses generated in the optimization of the cg200 engine (throttle cylinder).